2015
DOI: 10.1097/md.0000000000001485
|View full text |Cite
|
Sign up to set email alerts
|

A Large-Scale Study Indicates Increase in the Risk of Epilepsy in Patients With Different Risk Factors, Including Rheumatoid Arthritis

Abstract: Peripheral neuropathy and inflammatory reactions of the central nervous system may accompany rheumatoid arthritis (RA). Inflammatory processes play a critical role in epilepsy. Therefore, we conducted this study to determine the risk of epilepsy in patients with RA.The RA cohort comprised patients ages 20 years and older who were newly diagnosed with RA between 2000 and 2011, with data obtained from the Registry of Catastrophic Illnesses Patient Database. Patients without RA were frequency matched with an RA c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 43 publications
1
29
0
1
Order By: Relevance
“…The development of epilepsy within RA patients is 1.27-fold higher than the control patients without RA. Duration of non-steroidal anti-inflammatory drug (NSAID) therapy in RA patients negatively correlated with epilepsy development while patients with minimal NSAID therapy had a greater risk of epilepsy development [ 130 ]. This suggests that limiting the inflammatory process induced by RA reduces risk of epileptogenesis.…”
Section: Systemic Inflammationmentioning
confidence: 99%
“…The development of epilepsy within RA patients is 1.27-fold higher than the control patients without RA. Duration of non-steroidal anti-inflammatory drug (NSAID) therapy in RA patients negatively correlated with epilepsy development while patients with minimal NSAID therapy had a greater risk of epilepsy development [ 130 ]. This suggests that limiting the inflammatory process induced by RA reduces risk of epileptogenesis.…”
Section: Systemic Inflammationmentioning
confidence: 99%
“…RA is the most common form of autoimmune arthritis manifesting as a chronic inflammatory disease with involvement of joints and synovial membrane. Two population-based studies reported an increased risk of epilepsy in people with RA compared with controls [8,86]. The link between RA and epilepsy may be explained by vasculitis [87], CNS infections [88] and the use of methotrexate [89] and sulphasalazine [90].…”
Section: Rheumatoid Arthritis (Ra)mentioning
confidence: 99%
“…[32][33][34][35][36][37] Study characteristics Among the six included studies, four of them (n = 3,803,535 in total) were related to the comorbidity of epilepsy and RA [34][35][36][37] and the other two (n = 3,290,578 in total) focused on children born to mothers with RA. 32,33 Chang and colleagues 34 and Ong and colleagues 35 excluded a history of epilepsy before the diagnosis of RA. Téllez-Zenteno and colleagues 36 and Gaitatzis and colleagues 37 provided the prevalence of RA that preceded, cooccurred with, or followed the diagnosis of epilepsy.…”
Section: Study Selectionmentioning
confidence: 99%
“…The prevalence of epilepsy in RA and non-RA were extracted or calculated from the four included studies. [34][35][36][37] Since statistical heterogeneity among studies was significant (I 2 = 94.23% and p < 0.001), the random effects model was used. Results showed that RA was associated with an increased risk of epilepsy (0.83% in RA versus 0.44% in non-RA; RR 1.601; 95% CI: 1.089-2.354, p = 0.017; based on n = 3,803,535; Figure 2).…”
Section: Risk Of Epilepsy In Ra Patientsmentioning
confidence: 99%